Meningkatkan Motivasi Prestasi Belajar Mahasiswa Semester II Melalui Skenario Joyful Learning di Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto - Al-Mahali, Ahmad Mustofa Jalalluddin (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2017)
At least there are three main issues that underlie the reluctance of students to learn better. (1) learning technique problem that does not grow student's motivation, (2), lecturer's existence is not as a facilitator who teaches students, private auctions that teach or patronize, (3) delivery of instruction messages with less interactive and attractive media. By examining something that is in the field, there appears to be a discrepancy between learning by the method of learning it uses. Joyful Learning Scenario is usually done by lecturers so far only aspects of mastery of student concepts. For that need an assessment technique can reveal aspects of the process, one of them. The purpose of this research are: (1) To Know How to Improve Motivation of Student Achievement Semester II in Tarbiyah High School of Raden Wijaya Mojokerto, (2) To Know How Joyful Learning Scenario at Tarbiyah High School of Raden Wijaya Mojokerto (3) To Knowing How Efforts to Improve Student Achievement Motivation Semester II Through Joyful Learning Learning at Tarbiyah High School of Raden Wijaya Mojokert The subject of this research is the second semester students in the Islamic religious education program of Tarbiyah High School of Raden Wijaya Mojokerto academic year 2016/2017 . There are several things that need authors conclude (1) Group work is very effective done in order to support the activities of the lectures with a fun learning. (2) The provision of resource materials that students need to complete the task is very effective when the lectures are conducted using a fun learning lesson. (3) The balance of time efficiency with each group at the beginning and end of each lecture is essential in ensuring that the report card is really concise and interesting.